Analytical study of thyroid and prolactin hormone levels in infertile women with menstrual irregularities - Keerthanaa, S. R.; Hiremath, P. B. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Infertility is the inability of a couple to achieve pregnancy over an average period of one year (in a woman under 35 years of age) or 6 months (in a woman above 35 years of age) despite adequate, regular (3-4 times per week), unprotected sexual intercourse. It is of two types, primary infertility and secondary infertility. It can be due to the woman, the man, or both men and woman. Though there are several factors plays role in the causing infertility, endocrine hormones play a crucial role in it. Among all the hormones, thyroid and prolactin hormone have profound effects on reproduction and pregnancy. Methods: A prospective analytical study was conducted among 200 female patients, of age group 20-40 years, attending the outpatient department of obstetrics and gynecology. Sent for analysis of thyroid profile and prolactin levels. The data of the patients who have been completely followed up after six months was entered in excel sheet and analyzed using SPSS (version 16). Results: In this study the mean age of the study participants were 31.33±4.12 years and 4 of them were below 25 years of age. There is high prevalence of hypothyroidism (23.5%) and hyperprolactinemia (31%) was noted among the infertile females. Conclusions: The assessment of thyroid function and prolactin levels is mandatory in the work up of all infertile women, especially those presenting with menstrual irregularities. Also, early initiation of treatment may help in restoring the fertility among the infertile woman.